Effects of species vs. functional diversity: Understanding the roles of complementarity and competition on ecosystem function in a tropical stream fish assemblage. (January 2015) - Leduc, Antoine O.H.C.; da Silva, Eduardo M.; Rosenfeld, Jordan S.
Highlights: We measured fish growth in enclosures placed in a first-order tropical forest creek. We tested the effect of increasing functional diversity (feeding guilds) on growth. We found highest fish growth under high functional diversity treatments. Functional diversity led to complementarity in dietary resources use. Complementary use of dietary resources led fewer antagonistic interactions. Abstract: The positive effects of biodiversity on the functioning of ecosystems are well demonstrated in laboratory microcosms but the precise mechanisms underlying higher ecosystem process rates in natural assemblages are less well understood. We investigated, under semi-natural conditions (field enclosures), the potentially interactive effects of species identity and trophic function (i.e., feeding guild) on consumer growth, using a fish assemblage in a tropical stream. We tested the relative importance of species identity and trophic function on consumer growth by placing 2 fish of either (i) the same species, (ii) different species but of similar trophic function, or (iii) different species of different trophic functions in each of 72 stream enclosures for 48 days and measuring biomass change, individual diet composition and behavior. We predicted that if functional diversity had a larger impact than species diversity, then fish growth would be highest for pairs of species from different functional groups (i.e., those with the highest diet complementarity), intermediate for different species within a guild, and lowest for the same species (those with the lowest complementarity and highest niche overlap), such that functional variation between species in different guilds would exceed functional differences within guilds. Our results show that functional heterogeneity rather than species diversity per se had the greatest impact on food resources used complementarily, leading to higher biomass accrual. Mechanistically, higher growth rates were driven by concomitant increases in resource intake and reductions in antagonistic interactions. Together, these results underscore the importance of functional diversity on macroconsumer production in natural assemblages.